2019
DOI: 10.1002/btpr.2850
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a generic virus safety evaluation for monoclonal antibody investigational new drug applications

Abstract: Biologics produced from CHO cell lines with endogenous virus DNA can produce retrovirus‐like particles in cell culture at high titers, and other adventitious viruses can find their way through raw materials into the process to make a product. Therefore, it is the industry standard to have controls to avoid introduction of viruses into the production process, to test for the presence of viral particles in unclarified cell culture, and to develop purification procedures to ensure that manufacturing processes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For the effective virus removal and inactivation steps, virus filtration and low-pH inactivation are commonly used for mAb manufacturing. [8][9][10][11] Figure 1 shows a typical purification process for therapeutic mAbs. 9,[12][13][14] The virus filtration step is usually performed after polishing chromatography; thus, its feed solution conditions, such as mAb concentrations, pH, and ionic strengths, widely vary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the effective virus removal and inactivation steps, virus filtration and low-pH inactivation are commonly used for mAb manufacturing. [8][9][10][11] Figure 1 shows a typical purification process for therapeutic mAbs. 9,[12][13][14] The virus filtration step is usually performed after polishing chromatography; thus, its feed solution conditions, such as mAb concentrations, pH, and ionic strengths, widely vary.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Figure 1 shows a typical purification process for therapeutic mAbs. 9,[12][13][14] The virus filtration step is usually performed after polishing chromatography; thus, its feed solution conditions, such as mAb concentrations, pH, and ionic strengths, widely vary. To design a robust and high-throughput virus filtration step, optimization of the feed solution conditions and/or selection of an appropriate virus-retentive filter are required.…”
Section: Introductionmentioning
confidence: 99%
“…As continuous low‐pH VI achieves inactivation through mimicking plug flow regime in a tubular reactor, the ideal residence time is critical to ensure adequate VI, while avoiding degradation products arising from prolonged or localized exposure to low‐pH solution conditions (Gillespie et al, 2019; Jungbauer, 2019; Konstantinov & Cooney, 2015). Detergent‐mediated VI could thus provide an orthogonal means of VC for molecules sensitive to low pH and for next‐generation continuous bioprocessing with minimal risk of product degradation (Feroz et al, 2021; Sipple et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although inactivation screening studies can be conducted with surrogates, the final VC validation studies are typically conducted at third‐party sites and tend to have long turnaround time of 4–7 months. Thus, delay or failure to comply with VC validation requirements could hinder development, scale‐up, and commercialization, in particular for newer modality therapeutics, atypical process conditions, or newer virus inactivation (VI) agents (Feroz et al, 2021; Sipple et al, 2019). We propose an efficient and comprehensive strategy to screen VI conditions to reduce risks of VC validation failure, to ensure expedited drug delivery to clinical trial patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have expanded to develop a generic VI strategy to cover previously identified viral contaminants or virus models that have different physicochemical properties. [9] Although a wide range of virus species have been used, viruses from the Herpesviridae family have been interchangeably used to indicate the inactivation of herpesviruses by buffers, with a summary of VI studies shown in Table S1. Moreover, the enveloped viruses chosen for most of the studies were > 100 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%